Social control informal, legal and medical - Chriss, James J., 1955- (Bingley, U.K. : Emerald, 2010)
There has been a revitalization of interest in social control over the last decade, and this volume contributes to renewed attempts to explain and conceptualize social control in all its diversity. It provides a broad conceptualization of social control which is unique. Rather than concentrating solely on law and legal control (the criminal justice system), there are also treatments of informal control (socialization, group formation and the controls exerted in everyday life) as well as medical control (norms regarding health and illness, particularly with regard to notions of 'normal' behaviour). This volume brings together cutting edge analyses both theoretical and empirical of social control from leading scholars in the fields of sociology, criminology, and related social sciences. Perspectives on Social Control is of interest not only to sociologists and criminal justice practitioners, but also to medical professionals (primarily for the focus on medical control or medicalization), as well as a wide array of scholars from a variety of disciplines concerned with the socialization process and the pressures toward conformity exerted by social groups in everyday life.
Social control revisited / James J. Chriss -- 'Pass the trash : the mortgage default crisis as state-corporate crime / John Liederbach -- Sex offender registration and notification laws as a means of legal control / Deborah Koetzle Shaffer -- Freedom, social control, and the problem-solving court movement / James L. Nolan -- Social and ecological control : Ross's early contribution / Matthias Gross -- The technology and the artefacts of social control : monitoring criminal and anti-social behavior through and in media cultures / Stuart Connor, Richard Huggins -- Empowered communities or self-governing citizens? (Re)examining social control within the move toward community / Christopher D. O'Connor -- Social control in doctor-patient relationships : similarities and differences across medical specialities / Victor Lidz -- The social control of sex and food : a brief overview / James J. Chriss.
Keywords: Social control